eXile - Kinas, Fernando [UNESP] (Universidade do Estado de Santa Catarina, 2024)
Scenic script of the theatrical work eXílio, produced by Coletivo Comum, a group based in São Paulo. The work, with text and direction by Fernando Kinas, premiered in April 2024 and had runs at Teatro de Contêiner and Teatro Arthur Azevedo.
eXilio
eXílio
Keywords: Coletivo Comum; Dramaturgy; Exile; Scenic script